In situ detection of boron by ChemCam on Mars. Issue 17 (5th September 2017) - Gasda, Patrick J.; Haldeman, Ethan B.; Wiens, Roger C.; Rapin, William; Bristow, Thomas F.; Bridges, John C.; Schwenzer, Susanne P.; Clark, Benton; Herkenhoff, Kenneth; Frydenvang, Jens; Lanza, Nina L.; Maurice, Sylvestre; et al.
Abstract: We report the first in situ detection of boron on Mars. Boron has been detected in Gale crater at levels <0.05 wt % B by the NASA Curiosity rover ChemCam instrument in calcium‐sulfate‐filled fractures, which formed in a late‐stage groundwater circulating mainly in phyllosilicate‐rich bedrock interpreted as lacustrine in origin. We consider two main groundwater‐driven hypotheses to explain the presence of boron in the veins: leaching of borates out of bedrock or the redistribution of borate by dissolution of borate‐bearing evaporite deposits. Our results suggest that an evaporation mechanism is most likely, implying that Gale groundwaters were mildly alkaline. On Earth, boron may be a necessary component for the origin of life; on Mars, its presence suggests that subsurface groundwater conditions could have supported prebiotic chemical reactions if organics were also present and provides additional support for the past habitability of Gale crater. Key Points: First detection of boron on Mars' surface Presence of boron in Gale crater suggests evaporite deposits may be present stratigraphically above the detected boron Borates can stabilize ribose in aqueous solutions and thus may be important for prebiotic chemistry